Der Europäische Pass für Bankgeschäfte - Nemeczek, Heinrich (Mohr Siebeck, 2021)
Heinrich Nemeczek examines the doctrinal structure of the European passport for banking business in Germany. In particular, his analysis addresses the Single Supervisory Mechanism and regulatory flaws which may appear in connection with the provision of cross-border banking services in the European Single Market.
PublicationDate: 20211109
Keywords: Sozial- und Kulturwissenschaften -- EZB -- Bundesbank -- GWB-Novelle -- Schadensersatzrichtlinie -- SSM -- Eigenkapitalregulierung -- Eigenmittelregulierung -- Bankenaufsichtsrecht -- Wyhl -- Passporting -- incentive compensation -- CRR-Kreditinstitut -- Weltchristentum -- Verwaltungsrecht -- Besonderes Verwaltungsrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Europarecht